Building innovative tools - International Food Policy Research Institute (International Food Policy Research Institute, 2015)
IFPRI’s track record of strengthening food policy around the globe is due in no small part to innovation—particularly the development of novel models, methodologies, and tools for analysis and the develop¬ment and use of leading-edge platforms for sharing data.